Options for perioperative pain management in neurosurgery - Vadivelu N; Kai AM; Tran D; Kodumudi G; Legler A; Ayrian E (Journal of Pain Research, 2016)
Nalini Vadivelu,1 Alice M Kai,2 Daniel Tran,1 Gopal Kodumudi,3 Aron Legler,1 Eugenia Ayrian,4 1Department of Anesthesiology, Yale University School of Medicine, New Haven, CT, 2Stony Brook University School of Medicine, Stony Brook, NY, 3California Northstate University College of Medicine, Elk Grove, 4Keck School of Medicine of the University of Southern California, Los Angeles, CA, USA Abstract: Moderate-to-severe pain following neurosurgery is common but often does not get attention and is therefore underdiagnosed and undertreated. Compounding this problem is the traditional belief that neurosurgical pain is inconsequential and even dangerous to treat. Concerns about problematic effects associated with opioid analgesics such as nausea, vomiting, oversedation, and increased intracranial pressure secondary to elevated carbon dioxide tension from respiratory depression have often led to suboptimal postoperative analgesic strategies in caring for neurosurgical patients. Neurosurgical patients may have difficulty or be incapable of communicating their need for analgesics due to neurologic deficits, which poses an additional challenge. Postoperative pain control should be a priority, because pain adversely affects recovery and patient outcomes. Inconsistent practices and the quality of current analgesic strategies for neurosurgical patients still leave room for improvement. Given the complexity of postoperative pain management for these patients, multimodal strategies are often required to optimize pain control and at the same time limit undesired side effects. Keywords: acute pain, post surgical pain, post craniotomy analgesia